Local History Knowledge on Senior High School Students in Sukoharjo - Davena Salsabilla; Nur Fatah Abidin; Isawati (Criksetra: Jurnal Pendidikan Sejarah, 2024)
Abstrak: Local history refers to the history related to a specific region or area. This history includes events, figures, cultures, and traditions that are specific to that area. Local history is important because it helps understand the identity and cultural heritage of a society, and can be a source of inspiration and learning for future generations. The aim of this research is to determine the level of local history knowledge of students at senior high school number 2 in Sukoharjo. This research uses a combination research method (mixed method research), combining qualitative and quantitative methods. Data collection is done using observation and questionnaires. The respondents in this research are students of  grade XI social sciences program at senior high school number 2 in Sukoharjo. Purposive sampling method is used in this research. Method triangulation and source triangulation are used in data validity testing. This research uses descriptive statistics and interactive analysis as data analysis methods. The results show that the level of local history knowledge among students at students at senior high school number 2 in Sukoharjo is very low, which indicates the need for a change in the approach to teaching local history at the school. Therefore, there is a need to increase local history knowledge among at senior high school number 2 in Sukoharjo, one of which is by utilizing the web as a learning media for history. Abstrak: Sejarah lokal merujuk pada sejarah yang berkaitan dengan suatu daerah atau wilayah tertentu. Sejarah ini mencakup peristiwa, tokoh, budaya, dan tradisi yang spesifik hanya untuk daerah tersebut. Sejarah lokal penting karena membantu memahami identitas dan warisan budaya suatu masyarakat, serta dapat menjadi sumber inspirasi dan pembelajaran bagi generasi selanjutnya. Tujuan dari penelitian ini adalah untuk mengetahui tingkat pengetahuan sejarah lokal siswa SMAN 2 Sukoharjo. Penelitian ini menggunakan metode riset kombinasi (mixed method research), penggabungan antara metode kualitatif dan metode kuantitatif. Pengumpulan data dilakukan dengan menggunakan observasi dan angket. Responden dalam penelitian ini adalah siswa kelas XI IPS SMAN 2 Sukoharjo. Metode purposive sampling yang digunakan dalam penelitian ini. Triangulasi metode dan triangulasi sumber digunakan dalam metode pengujian keabsahan data. Penelitian ini menggunakan statistik deskriptif dan analisis interaktif sebagai metode analisis data. Hasil penelitian menunjukkan bahwa tingkat pengetahuan sejarah lokal pada siswa SMAN 2 Sukoharjo sangat rendah yang dapat mengindikasikan perlunya perubahan dalam pendekatan pengajaran sejarah lokal di sekolah tersebut. Oleh karena itu, perlu adanya peningkatan pengetahuan sejarah lokal pada siswa SMAN 2 Sukoharjo, salah satunya dengan memanfaatkan web sebagai media pembelajaran sejarah.